Asking for action or information? Crosslinguistic comparison of interrogative functions in early child Cantonese and Mandarin. Issue 3 (June 2015) - Li, Hui; Wong, Eileen Chin Mei; Tse, Shek Kam; Leung, Shing On; Ye, Qianling
Request for information (RfI) is believed to be the universally dominant function of young children's questioning, whereas request for action (RfA) has been reported to be the leading interrogative form used in early child Cantonese. The possibility of crosslinguistic variability prompts further research and comparison with additional languages. This study compares the interrogatives elicited from two early Chinese language corpora: Early Childhood Cantonese Corpus (ECCC) and Early Childhood Mandarin (ECMC). Altogether, 1214 and 942 question types were elicited from ECCC and ECMC, respectively. Analyses indicated that: (1) all the interrogative functions identified in an earlier study of Cantonese were also observed in the early Mandarin interrrogatives; and (2) both RfA (49.9%) and RfI (45.5%) were the most frequently observed functions of early child Chinese interrogatives. This crosslinguistic evidence suggests that follow-up studies are needed to further explore the possible influences of language, culture and communication tasks on children's uses of interrogative forms.